CULTURAL COLLISION AND COLONIAL POWER: A POSTCOLONIAL READING OF CHINUA ACHEBE’S THINGS FALL APART - Nofansyah; Latumeten, Anna Anganita Theresia; Janah, Ulum (Prologue: Journal on Language and Literature, 2025)
This study explores Chinua Achebe’s Things Fall Apart through the lens of postcolonial literary theory, focusing on the cultural, ideological, and psychological impacts of colonialism on indigenous Igbo society. The novel, often regarded as a foundational postcolonial text, reveals the complexities of cultural identity, resistance, and displacement in the face of European imperial domination. Through close textual analysis, the research highlights how Achebe deconstructs colonial narratives and reclaims African voice and agency. This paper also investigates the nuanced portrayal of hybrid identities, the clash between tradition and modernity, and the broader implications of colonial disruption. Ultimately, the study affirms Things Fall Apart as a powerful literary act of resistance against the hegemonic structures of Western imperialism